Factors Affecting Technology Adoption of Geoisolator on Solar Saltworks in East Java Province - Aminah Happy Moninthofa Ariyani; Harianto Harianto; Suharno Suharno; Yusman Syaukat (Agriekonomika, 2020)
Large quantity and high-quality salt are demanded in Indonesia, yet the quality of salt produced by farmers is still low. Increasing salt quantity and quality is possibly done through the implementation of geoisolator technology. This study aimed to investigate factors affecting the decision of salt farmers to adopt geoisolator technology. The study was conducted at the salt production center in Madura Island. A survey on salt farmer was carried out during August-September 2018. A total of 190 respondents consisted of 131 salt farmers who adopted geoisolator technology and 59 traditional salt farmers were selected as a sample in this study. Factors affecting farmer decision to adopt geoisolator technology was analyzed using logit (logistic regression) model. The result of this study showed that the decision of salt farmer to adopt geoisolator technology was affected by the number of productive-age family members and the number of dependent family members, land area, farmer participation in the group, farmer participation in extension. Enhancement in the adoption of geoisolator technology needs synergy between extension agent and salt farmer group so that the mentoring process and knowledge transfer will be achieved.